A Multi Criteria Decision-Making for Improving Cooling Tower Reliability: An Application of Value-Focused Thinking and Analytical Hierarchy Process at PT KPI - Willy Pradhana; Pri Hermawan (Riviera Publishing, 2026)
This study addressed the strategic need to improve cooling tower reliability at PT KPI, where an aging timber structure had experienced progressive deterioration due to prolonged exposure to moisture, chemical effects, biological degradation, and continuous operational loading. As the cooling tower supports cooling water circulation and power generation processes, its failure could disrupt refinery operations and result in significant operational and financial impacts. The purpose of this research was to determine the most appropriate maintenance and improvement strategy by integrating stakeholder expectations with technical, operational, financial, and implementation considerations. This study employed a mixed-method approach involving semi-structured interviews, questionnaires, field observations, document reviews, Value-Focused Thinking (VFT), the Analytic Hierarchy Process (AHP), and Cost–Benefit Analysis (CBA). The results showed that operational continuity was the most important criterion, followed by technical reliability, economic performance, implementation constraints, and maintainability. Three alternatives were evaluated: constructing a new reinforced concrete cooling tower, revitalizing the existing timber structure, and replacing structural components with a Fiber-Reinforced Polymer (FRP) system. The AHP synthesis identified timber revitalization as the most preferred alternative, with the highest global priority score and the strongest cost–benefit value. Sensitivity analysis confirmed that this ranking remained stable across all evaluated scenarios. The study concluded that phased timber revitalization was the most feasible strategy for enhancing cooling tower reliability while maintaining refinery operational continuity.